The military potential of the Morlachs of Dalmatia in the French sources form the beginning of the 19th century - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2022)
Between 1806 and 1813 Dalmatia became part of the French Empire. The province, whose continental part was inhabited by Vlach shepherds called Morlachs, was economically inefficient, which was a huge problem to the new administration. Various projects of the economic development of Dalmatia had already been drawn up under Venetian rule, but their implementation took time and the collection of taxes had to be regular in the face of the constant wars waged by the French Empire. Hence, the French authorities were convinced that the only form of any kind of financial compensation for their dominion over Dalmatia would be military conscription. The short period of French rule in Dalmatia resulted in analyses concerning the possibility of exploiting the military potential of the Vlach shepherds, which became a kind of summary of all previous considerations concerning this problem. Indeed, the French administrators ruled over areas where the traditional military duties of the Vlach settlers were used in very different ways. Hence, many of those analysis made by the French include a broader historical account of the evolution of Vlach communities in the borderlands of Dalmatia, Bosnia, and Croatia.